Prognostic Factors for Small Cell Neuroendocrine Carcinoma of the Uterine Cervix: An Institutional Experience. Issue 2 (1st February 2014) - Intaraphet, Suthida; Kasatpibal, Nongyao; Siriaunkgul, Sumalee; Chandacham, Anchalee; Sukpan, Kornkanok; Patumanond, Jayanton
Abstract : Objective: This study aimed to determine the clinicopathologic characteristics that affected the survival in patients with small cell neuroendocrine carcinoma of the uterine cervix (SNEC). Materials and Methods: All patients with SNEC treated at Chiang Mai University Hospital between January 1995 and October 2011 were retrospectively reviewed with histologic confirmation of SNEC diagnosis. The prognostic predictors for survival were assessed using competing risk regression analysis concerning the probabilities of competing events. Results: One hundred thirty histologically confirmed patients with SNEC met the study criteria. The median overall survival and median cancer-specific survival (CSS) for entire group were 47.8 and 58.1 months, respectively. Five-year CSS for patients with early-stage disease was 62.6% and for patients with advanced-stage disease was 18.1% ( P < 0.001). Among the patients with surgically treated early-stage disease, those with adjuvant chemotherapy had a better 5-year survival rate than those with surgery alone, those with adjuvant radiotherapy, and those with adjuvant chemoradiation therapy ( P = 0.041). In multivariable analyses, decreased survival in patients with early-stage disease was associated with age older than 60 years at diagnosis (hazards ratio [HR], 4.9; P = 0.007) and deep stromal invasion (HR, 2.9; P = 0.011). Among the patients with advanced-stage disease, decreased survival was associated with age at diagnosis (older than 60 years: HR, 9.9; P < 0.001 and younger than 45 years: HR, 3.4; P = 0.035) and International Federation of Gynecology and Obstetrics stage IV (HR, 7.4; P = 0.024). Conclusions: International Federation of Gynecology and Obstetrics stage, age at diagnosis, and deep stromal invasion were important prognostic factors for CSS in patients with SNEC. Adjuvant chemotherapy may provide survival benefits in surgically treated patients with early-stage SNEC.